Sintesis Karbon Aktif dari Kulit Jeruk dengan Aktivasi Menggunakan Subkritik Air - Arenst Andreas (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Low-cost and environmental friendly activated carbon was synthesized from orange peels (citrus nobilis var. microcarpa) which activated by subcritical water. Orange peels were first carbonized in an electrical furnace at temperature of 800oC for 2 hours. Activation process of the carbonized orange peel were done in 1 hour inside a reactor at temperature of 200oC and pressure from 120 to 220 bar. Mesoporous activated carbon with highest surface area was obtained at pressure of 170 bar, where the surface area was 491.840 m2/g. The orange peel derived activated carbons were tested in the adsorption of methylene blue (MB) from aqueous phase. The adsorption study was done under batch condition with various initial concentration of MB solution. The initial concentrations of MB used were 2, 4, 6, 8 and 10 ppm. The adsorption of MB followed the pseudo-second-order rate equation, and fit well to the Temkin isotherm, while the adsorption mechanism was affected by the intraparticle diffusion and surface diffusion.